Institutional modelling of integrated PPT system in urban agglomerations - Smojver, Željko (Array, 2018)
Urban agglomerations (centres with gravitating settlements in the suburbs) are examples of overpopulated urban structure with almost permanent peak load. Selection of public transport is the fundamental issue in planning the expansion of the existing one, or in constructing a new form of urban public transport system. Achieving a higher level of using mass public transport can also be inspired by building intermodal terminals (e.g. bus-train/urban railways/-car). However, apart from the urban railway, funicular, bicycle subsystem and maritime transport should be included as alternative public transport modalities as well. According to the problem described in this scientific paper, the suggested model is that of integration of all forms of public passenger service with a unique organisation, unified payment collection, integrated timetable, all included into a unique information system. The results of research in this paper indicate that the first step of integration of the public passenger transportation implies founding regional transport administration.